Psychological Profile and The Problems of Adolescence and Protective Health Care Services - Onar, Gizem; Odabaş, İrem Saadet; Canbolat, Zeynep (Turkey Health Literacy Journal, 2021)
According to the World Health Organisation, adolescence covers the period between the ages 10 and 19. Physical development, sexual maturation and psychosocial change and development are observed in this period even if these are variable due to the societies, eras and personal traits. Adolescence is splitted to three phases since each phase has its own characteristics: early adolescence (ages between 12-14), middle adolescence (ages between 15-17) and late adolescence (18 years and older). Mental physiological changes are observed in this period in which person begins to form a new personality. Also, mood and eating disorders, anxiety and drug addiction are commonly and frequently observed. Since these changes occur quickly, it is possible to face with some mistakes in differentiation between pathological and physiological symptoms. For this reason, it is important to know the specifications of each period. However, the most significant issue is to provide adolescents with a medium in which they are able to handle this specific period of life healthfully. At this point, protective health care services are run by families, teachers, governors and the ones that may have any possible effects upon the adolescents. This compilation aims to emphasise the significance of awareness related to the period and providing protective health care in keeping adolescents' mental health in a good condition.
Keywords: Adolescent; psychology; adolescence; mental health; protective health care